Impact of myotomy length on per-oral endoscopic myotomy (POEM) outcomes for achalasia: a meta-analysis of randomized trials - Wu, Yizhong; Grieme, Alexander; Garza, Manuel; Smith, Eric R; Beran, Azizullah; Bushe, Bryce; Han, Andrew; Qatomah, Abdulrahman; Spadaccini, Marco; Tringali, Alberto; Kunovský, Lumír; Al-Haddad, Mohammad A; et al. (Surgical endoscopy, 2025)
INTRODUCTION: Peroral endoscopic myotomy (POEM) has been established as a safe and effective intervention for Type I and II achalasia. Studies have shown that short POEM is non-inferior to long POEM, with some evidence of decreased incidence of gastroesophageal reflux disease (GERD). This meta-analysis aims to systematically review and analyze randomized controlled trials (RCTs) data comparing clinical and safety outcomes for long and short POEM procedures while further investigating differences in GERD and other long-term clinical outcomes. METHODS: We conducted a comprehensive search in PubMed, Embase, Cochrane, and Web of Science from inception until October 2024 for RCTs comparing long and short POEM procedures for the treatment of achalasia. Our pooled data was analyzed for clinical and objective procedural success, procedural adverse events, GERD outcomes, procedure time, and hospitalization time. A random effects model was used, and the data was presented using pooled odds ratios (OR) and mean differences (MD) with 95% confidence intervals (CI). RESULTS: Five RCTs were included with 518 achalasia patients (253 in short group and 265 in long group). Baseline characteristics of enrolled patients were similar across studies. Short and long POEM had similar clinical success (OR 1.18, 95% CI: 0.45-3.06, p = 0.73, I2 0%), procedural adverse events (OR 0.72, 95% CI: 0.33-1.54, p = 0.39, I2 0%), hospitalization time (0.14 days, 95% CI: - 0.13 to 0.40, p = 0.31, I2 0%). Short POEM had shorter procedure time (MD - 16.68 min, 95% CI: - 22.77 to - 10.59, p < 0.00001, I2 75%). The groups had similar symptomatic GERD (OR 0.86, 95% CI: 0.52-1.44, p = 0.57, I2 0%), however short POEM had significantly lower acid exposure time (OR 0.62, 95% CI: 0.38 to 0.99, p = 0.04, I2 0%) and erosive esophagitis after sensitivity analysis (OR 0.52, 95% CI: 0.27 to 1.01, p = 0.05, I2 0%). CONCLUSION: Our study demonstrates that short POEM is clinically non-inferior to long POEM but has advantages in shorter procedure time and lower odds of objective evidence of gastroesophageal reflux disease.
Keywords: endoskopické operace přirozenými otvory; Reflux; Natural Orifice Endoscopic Surgery; Esophageal Achalasia; randomizované kontrolované studie jako téma; Postoperative Complications; Pyloromyotomy; Humans; achalázie jícnu; gastroezofageální reflux; pyloromyotomie; Myotomy; Achalasia; Endoscopy; Gastroesophageal Reflux; POEM; Randomized Controlled Trials as Topic; Operative Time; lidé; myotomie; Treatment Outcome; výsledek terapie; délka operace; pooperační komplikace